OVERVIEW OF ORGANIZATIONAL CULTURE AT AN-NISA HOSPITAL TANGERANG: Bahasa Indonesia - Ediansyah; Pertiwi, Retno Indah; Nitzah; Azzhara, Fia (Homes Journal = Hospital Management Studies Journal, 2024)
Background: Identifying organizational culture is crucial for an organization as it can boost overall productivity. Organizations in the economic, social, and educational sectors have extensively identified their cultures, but few hospitals in Indonesia have followed suit.Objective: To determine the culture that is currently felt and preferred by employees at AN-NISA Hospital Tangerang.Methods The research method used quantitative descriptive analysis by distributing questionnaires to 266 respondents who were permanent employees of AN-NISA Hospital Tangerang.Result: The results of the study show that the current organizational culture at AN-NISA Hospital Tangerang is Clan, with an average of 38.42, and the preferred culture at AN-NISA Hospital Tangerang is Clan and Market, with an average of 27.11 and 25.49.Conclusion: AN-NISA Hospital Tangerang will continue to consider the institution as a second home, family, and open to telling stories about themselves. However, AN-NISA Hospital Tangerang hopes to have leaders who can set an example as individuals who are serious, focused, aggressive, and results-oriented. Growth, innovation, and achievement of goals were aggressively developed to make AN-NISA Hospital Tangerang an excellent hospital among the others.